(untitled) (Research, Society and Development, 2021)
The study consists of the state of knowledge developed in the doctoral thesis of the Graduate Program of the Federal University of Santa Maria (UFSM/RS), based on the descriptors: “Permanent Teacher Education”, “Special Education” and “Inclusive Teaching”. These descriptors were chosen because they are constituents in the research title "Permanent Education in Special Education: approaches and departures from Inclusive teaching". The methodology used was bibliographic research, with a qualitative approach, in search of what has already been produced in relation to research questions. In this sense, it provides the contextualization of the object of study located in the historical, social and scientific context. The articles found make important provocations for the area of, Special Education as a field of knowledge, in the most diverse dimensions, such as: “polyvalence” through training, both in the initial and in the continuing; the pedagogical / epistemological emptying through lightened training for the SES; Teacher Training in the theoretical foundations for problematizing praxis; Special Education as a field of knowing how to be treated superficially, being placed only in the imperative of the perspective of inclusive education, still, the Training of Teachers for inclusion, in the search for methodologies, techniques and procedures for inclusion. From this "panning" of the descriptors in the aforementioned repositories, in the research endorsed in this state of knowledge and in the Special Education Journals of UFSM, it was possible to find important gaps to be researched due to the little and / or lack of scientific publications in the context of permanent teacher training for inclusive teaching, as proposed in the investigation.